Antibacterial study of 5 primary rainforest plants from Malaysia and isolation of selective antibacterial constituents from Burkillanthus malaccensis (Ridl.) Swingle - Mahbub, Nuzum (2021)
It has now become the necessity to search for novel and more effective antibacterial compounds due to the constant progression of bacterial resistance to currently available antibiotics. Attainment in this regard has focused on tropical plants because of their ability to produce a potential spectrum of biologically active molecules. The tropical rainforest of Malaysia delivers extensive unexplored biodiversity of natural resources which is contemplated as one of the most developed ecologies worldwide. Aim of this project is to search for at least one new antibacterial pure compound from rare medicinal plants and to elucidate their mechanism of action specifically against Gram-negative bacteria.